Deterministic and stochastic analysis of a prey–predator model with herd behaviour in both. Issue 1 (1st January 2016) - Maiti, Alakes; Sen, Prosenjit; Samanta, G. P.
ABSTRACT: This paper aims to study the dynamical behaviours of a prey–predator system, where both the prey and predator show herd behaviours. Positivity, boundedness, stability of equilibrium points, et cetera, are discussed in deterministic environment. To incorporate the effect of fluctuating environment, we have perturbed the birth rate of prey species and death rate of predator species by Gaussian white noises. Then the resulting model is cultured by the method of statistical linearization to study the stability and non-equilibrium fluctuation of the populations in stochastic environment. Numerical simulations are carried out to validate our analytical findings. Implications of our analytical and numerical findings are discussed critically.